Spiritual Connections and Complexities in Rural Communities: A Case Study of Annang Farmers in Akwa Ibom State, Nigeria - Solomon, Valerie Aphie; Yaro, Margaret Abba; Ekong, Ifiok David (International Journal of Humanities and Social Science Research, 2015)
The study examined spiritual and religious connections and complexities in rural communities using the indigenous Annang people of Akwa Ibom state as a case study. The research made use of primary data from 150 randomly selected respondents and 8 purposively selected key informants, using questionnaires and interview schedules. Data analysis was both descriptive and inferential. Findings indicate that 94% of the respondents were aged between 21 and 60years, 94% had some form of formal schooling, all respondents were Christians, with 61.3% being married and 92% earning a maximum of NGN50, 000 monthly, and 52% of respondents had farming as their primary occupation. Respondents were highly inclined to spirituality with a total mean score of 28.84, and 98.7% of respondents attending religious functions at least once a week, and a further 62.7% relying on fate, miracles and protection from charms and amulets. The multiple regression results showed that there was no significant relationship between selected sociological factors and respondent’s inclination to spirituality, while the T-test analysis statistically proved that there was no difference in the inclination to spirituality between men and women with a -1.21 t-calculated value and 1.96 critical value. The study recommends that education with focus on the enlightenment, re-orientation, and counselling of individuals on the subject matter be effectively initiated to reduce the levels of inclination to spirituality. The study examined spiritual and religious connections and complexities in rural communities using the indigenous Annang people of Akwa Ibom state as a case study. The research made use of primary data from 150 randomly selected respondents and 8 purposively selected key informants, using questionnaires and interview schedules. Data analysis was both descriptive and inferential. Findings indicate that 94% of the respondents were aged between 21 and 60years, 94% had some form of formal schooling, all respondents were Christians, 61.3% being married and 92% earned a maximum of NGN50, 000 monthly. 52% of respondents had farming as their primary occupation. Respondents were highly inclined to spirituality with 98.7% of respondents attending religious functions at least once a week and a further 62.7% relying on fate, miracles and protection from charms and amulets. The multiple regression results showed that there was no significant relationship between selected sociological factors and respondent’s inclination to spirituality, while the T-test analysis showed that there was no difference in the inclination to spirituality between men and women. The study recommends that formal education with focus on the enlightenment, re-orientation, and counselling of individuals be effectively initiated to reduce the levels of inclination to spirituality. This will ensure that local level decision making is objective and based on facts.